Does Hip Fracture Admitting Service Affect Proper Deep Venous Thrombosis Prophylaxis? An Investigation at a Level 1 Trauma Center. Issue 12 (December 2022) - Diedring, Ben; Knapp, Paul; Bandovic, Ivan; Druskovich, Katherine; Waldron, Jacob; Denisiuk, Marek; Frisch, Nicholas; Afsari, Alan; Hayward, Richard; Best, Benjamin
Abstract : Objective: To examine if rates of appropriate thromboprophylaxis prescribing at the time of discharge would be higher in patients admitted to the orthopaedic service. Second, to see if improvements could be made in the rates of these missed events after a structured intervention. Design: Retrospective Cohort Study, Prospective Interventional. Setting: Level 1 Academic Hospital. Patients: Two hundred forty-six patients undergoing a hip hemiarthroplasty for femoral neck fracture discharged to an extended care facility. Intervention: A letter was sent to the internal quality control committee detailing our preintervention study. Main Outcome Measure: We looked at the differences among admitting services for missed thromboembolic prophylaxis (TPx) at the time of hospital discharge and rates of appropriate TPx after a structured intervention. Results: No statistically significant differences existed in relation to patient age, gender, body mass index, or postoperative discharge day in the preintervention group. Orthopaedic surgery prescribed adequate TPx at discharge for 76 of 77 patients (98.7%), general trauma surgery for 26 of 30 patients (86.7%), and internal medicine for 85 of 96 patients (86.7%) in the preintervention group. There was a statistically significant difference when comparing adequate TPx between orthopaedic surgery and other services ( P < 0.013 and <0.021, respectively). Our postintervention data found a significant decrease in the rates of missed TPx on discharge. In our preintervention sample group compared with our postintervention sample group, we saw a decrease in missed TPx of 5/39 versus 0/43 events ( P = 0.021). Conclusions: We found that a letter sent to all members of a hospital internal quality committee decreased incidences of missed TPx. Specifically, this letter explained the details of our study that kept track of rates of missed TPx among different admitting services. We found that after our intervention, which consisted of a letter and a multidisciplinary discussion, the rate of missed thromboembolic prophylaxis events improved from 5/39 (12%) to 0/43 (0%) ( P = 0.021). Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.